Manajemen Pembinaan Klub Bulutangkis di Kabupaten Demak - Billy Saputra Saputra; Bertika Kusuma Prastiwi; Yulia Ratimiasih (Journal of Physical Activity and Sports (JPAS), 2021)
The background of this research is based on: 1) How is the state of badminton club management in Demak/, 2) What is the pattern of coaching and training carried out by badminton clubs in Demak district?, 3) How are the human resources in badminton clubs in Demak district? , 4) What are the achievements of badminton clubs in Demak district?. The purpose of this study was to find out how good management is in badminton clubs in Demak district. The population of this research is the managers and coaches of badminton clubs in Demak district. The results of the planning of each club under study are different but the goal is the same. This is known by the researchers proved during the interview. The results of organizing show that there is a lack of transparency by researchers. The results of the nursery show that each club has its own method. The results of supervision show that it is said to be sufficient to supervise the exercise. The results of the evaluation of each club showed that it was implemented well. Leadership results show that each club has sufficient leadership. The conclusion of the study shows that the state of badminton club management in Demak district has not been going well. The pattern of coaching and training is said to be sufficient. Suggestions with the routine training carried out and the pattern of theoretical development, namely starting from problems, breeding and improving achievement. Keywords: Management, Coaching, Badminton Abstrak Latar belakang penelitian ini didasari dengan: 1) Bagaimana keadaan manajemen klub bulutangkis  di kabupaten Demak/, 2) Bagaimana pola pembinaan dan pelatihan yang dilakukan klub bulutangkis  di kabupaten Demak?, 3) Bagaimana sumber daya manusia yang ada  di klub bulutangkis di kabupaten Demak ?, 4) Bagaimana pencapaian prestasi yang sudah diraih klub bulutangkis di kabupaten Demak?. Tujuan penelitian ini untuk mengetahui bagaimana manajemen yang baik di klub bulutangkis di kabupaten Demak. Populasi peneltian ini adalah pengurus dan pelatih klub bulutangkis di kabupaten Demak. Hasil perencanaan dari tiap klub yang diteliti yaitu berbeda-beda akan tetapi tujuannya sama. Hal ini di ketahui dengan peneliti membuktikan ketika wawancara. Hasil pengorganisasian menunjukkan bahwa kurangnya transparan oleh peneliti. Hasil pembibitan menunjukkan kalau tiap klub memiliki metode sendiri. Hasil pengawasan menunjukkan bahwa dikatakan cukup untuk mengawasi latihan. Hasil evaluasi tiap klub menunjukkan bahwa terlaksana dengan baik. Hasil kepemimpinan menunjukkan bahwa masing-masing klub memiliki kepemimpinan yang cukup. Kesimpulan penelitian menunjukkan bahwa keadaan manajemen klub bulutangkis di kabupaten Demak belum berjalan dengan baik. Pola pembinaaan dan pelatihan dikatakan cukup. Saran dengan adanya latihan rutin yang dilakukan  dan pola pembinaan teori, yaitu mulai dari pemasalahan, pembibitan dan peningkatan prestasi..